Piezoelectric poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) microspheres for collagen regeneration and skin rejuvenation - Fu, Zeyu; Qu, Yingwei; Wu, Yinghao; Xu, Yuan; Zhang, Hengdi; Tang, Yaozong; Jin, Ziying; Zhao, Jia; Tan, Chang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSkin aging is an inevitable physiological process driven by factors like cellular senescence, ultraviolet radiation (UV) radiation, and environmental pollutants. A key feature is the accelerated collagen degradation in the dermal extracellular matrix, leading to visible signs such as sagging, wrinkles, and hyperpigmentation. Traditional fillers, such as hyaluronic acid and collagen-based fillers, offer only temporary volume enhancement without stimulating collagen regeneration. Studies have shown that electrical signals generated by piezoelectric materials can promote tissue regeneration.MethodsThis study explored the potential of piezoelectric PHBHHx microspheres as an innovative skin filler for enhancing collagen regeneration and improving maxillofacial aesthetics, with the aid of low-intensity pulsed ultrasound (LIPUS) stimulation. A comprehensive characterizations of the piezoelectric PHBHHx microspheres were conducted, and their potential to stimulate collagen regeneration was assessed using a subcutaneous injection model in New Zealand white rabbits.ResultsThe results indicated that PHBHHx microspheres exhibited stable degradation properties, great piezoelectric properties and excellent biocompatibility. Moreover, when stimulated by LIPUS, the collagen-regenerating effect of PHBHHx microspheres was further enhanced, histological analysis revealed a denser and more organized collagen structures in LIPUS-stimulated PHBHHx group.DiscussionThese findings highlight the potential of PHBHHx microspheres as an advanced biomaterial for applications in aesthetic medicine, particularly in promoting collagen regeneration and enhancing skin rejuvenation.